If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+4=6x+6-3x
We move all terms to the left:
9x+4-(6x+6-3x)=0
We add all the numbers together, and all the variables
9x-(3x+6)+4=0
We get rid of parentheses
9x-3x-6+4=0
We add all the numbers together, and all the variables
6x-2=0
We move all terms containing x to the left, all other terms to the right
6x=2
x=2/6
x=1/3
| 5x^2=200-15x | | -25=-5x-3+7x | | 1/12x-1/12=1/8+1/6-1/6x | | 2x-x-2/4=5x/8+5 | | 3(z+5)+3z=135 | | 5(x+3)=2(x+9 | | 5x3=25 | | 16=-2c–6c | | -4=-r+1/3 | | 5x=12=3x-6 | | 9x=6=32 | | 8x+9=3x+15 | | -3=-9+u/6 | | 5.5x+33=57 | | x-78=27 | | -3u+24=9(u-4) | | (1/5)^2x=15625 | | b+55=16 | | x-78=x | | -24=-5a–3a | | x(1+0.08)^17=150000 | | |z-3|=8 | | -u/2-15=-16 | | 6(u+3)=18 | | u7+13=16 | | 1=-6+c/5 | | -48=-2b+6b | | 2x(4x+3x)=21 | | x/16-21=18 | | 91=2k+3(k+2) | | -1=u–12 | | 42-23-1+3x=18 |